Interactive learning on increasing knowledge of midwifery master’s students on curriculum and transformational learning - Ari Indra Susanti; Anis Novitasari; Harridhil Silmi; Lindya Okti Herbawani (Curricula: Journal of Curriculum Development, 2025)
The transformation of higher education encourages the adoption of active and meaningful learning methods. In midwifery education, students must have a deep understanding of the curriculum and transformational learning approaches to become effective educators and agents of change. One effective strategy is interactive learning, which promotes active student engagement. This study aimed to examine the effect of interactive learning methods on improving the knowledge of Master of Midwifery students regarding transformational curriculum and learning. Using a quantitative cross-sectional design, the research was conducted in March 2025 with 44 students who were purposely selected. Pre-tests and post-tests were administered via Google Forms before and after an interactive learning session delivered through an online general lecture via Zoom. The Wilcoxon test results showed a significant increase in knowledge scores after the intervention. The findings demonstrate that the interactive learning method effectively enhances students' understanding and is well-suited for integration into midwifery education, particularly within a transformational curriculum. This method can be adopted as a strategic learning approach to strengthen conceptual comprehension among students and support the development of future midwifery educators.   Abstrak Transformasi pendidikan tinggi mendorong dosen dan institusi untuk menerapkan metode pembelajaran yang aktif dan bermakna. Dalam pendidikan kebidanan, mahasiswa perlu memahami kurikulum dan pendekatan pembelajaran transformasional secara mendalam agar dapat berperan sebagai pendidik dan agen perubahan. Salah satu strategi yang efektif adalah interactive learning, yang mendorong keterlibatan aktif mahasiswa dalam proses belajar. Penelitian ini bertujuan menganalisis pengaruh metode interactive learning terhadap peningkatan pengetahuan mahasiswa S2 Kebidanan mengenai kurikulum dan pembelajaran transformasional. Peneliti menggunakan pendekatan kuantitatif dengan desain cross-sectional dan melaksanakan studi ini pada Maret 2025. Sebanyak 44 mahasiswa dipilih melalui teknik purposive sampling. Peneliti membagikan pre-test dan post-test melalui Google Form sebelum dan sesudah pelaksanaan kuliah umum berbasis interactive learning secara daring melalui Zoom. Hasil uji Wilcoxon menunjukkan adanya peningkatan signifikan pada skor pengetahuan setelah intervensi. Temuan ini membuktikan bahwa metode interactive learning secara efektif meningkatkan pemahaman mahasiswa dan layak diintegrasikan ke dalam pendidikan kebidanan berbasis kurikulum transformasional. Metode ini dapat menjadi strategi pembelajaran yang memperkuat pemahaman konseptual dan mendukung pengembangan calon pendidik bidan di masa depan. Kata Kunci: kurikulum dan pembelajaran; pembelajaran Interaktif; pengetahuan